TANGGUNG JAWAB DIREKSI DALAM PENERAPAN GOOD CORPORATE GOVERNANCE BERDASARKAN UNDANG-UNDANG NO. 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - ARYA PRAYOGA, I KETUT; WIRYAWAN, I WAYAN; DEWI KASIH, DESAK PUTU (Kertha Desa, 2013)
The provisions on good corporate governance in Law. 40 of 2007, not yet firmly set in the articles of Limited Liability Company Act is only set implicitly. A more comprehensive arrangement can be found in the Decree of Minister of State. KEP-117/M-MBU/2002 on the Application of Good Practice on Corporate Governance of State Owned Enterprises (SOEs). Responsibilities of directors in implementing good corporate governance is concerned with the provision that the directors are fully responsible for the management company for the benefit of the company in accordance with the company's goals and objectives in terms of the implementation of good corporate governance directors in good faith and responsibly carry out their duties in the interest and effort company and are solely responsible for the accuracy and concordance any data or information provided by the company to the public (society). And if there is a loss due to the negligence and mistakes of directors may be held jointly and severally responsible.
Keywords: Directors Responsibility, Good Corporate Governance, Limited Liability Company.